Intoksikasi Alkohol Akibat Minuman Keras Oplosan - Pradana, Genta; Priyono, Drajad (Jurnal Kesehatan Andalas, 2021)
The incidence of alcoholic liquor poisoning (alcoholic liquor) in Indonesia shows a high number. One of the causes of alcohol poisoning is methanol. Methanol poisoning in Indonesia usually occurs as a result of drinking mixed alcohol liquor. It has been reported a male 23 years old with decreased consciousness after drinking oplosan alcohol suspected to contain methanol. The examination reveals that patients has metabolic acidosis, toxic optic neuropathy (TON) and erosive gastritis. Treatment was acidosis correction, prevent formation of metabolites, hemodialysis with supportive and symptomatic teraphy .Keywords: methanol, poisoning, alcohol mixed liquor